Conceptions of Social Institutions : in education, religion and family - Yogi Muhammad Akbar, Yogi Muhammad (Universitas Negeri Medan, 2024)
Study of The Concept of Social Institutions, is very important to study in more depth. This is because this study never stops being debated, disputed and discussed among the public. This paper wants to understand 3 things: First, the conception of social institutions... Second, the classification of social institutions... Third, the category of institutions. The research method used is library research using a descriptive qualitative approach. The results found are 3 things: First, understanding. .there are 3 definitions of Social Institutions: (1) Social institutions are a collection of values and norms that regulate human life. (2) a social institution is a system that shows that social roles and norms are interrelated to satisfy a social desire or function. (3) social institutions are a system of behavior and relationships that are centered on activities to meet the complexity of needs in people's lives. Second, the conceptual classification of social institutions. there are 3: (1) education (2) religion.(3) about family. Third, there are 3 categories of social institutions: (1).. Islamic educational institutions, Formal and Non-Formal Islamic education,.(2) contains religious institutions in zakat institutions, Extension institutions Religion, MUI, NU, Muhammdiyah, (3) regarding family institutions, namely biological family, surrogate family. The conclusion of this shows that social institutions cover many things, not only limited to small groups but also cover large groups